DIGITAL-THEOLOGICAL CONSCIOUSNESS: A MODEL OF ISLAMIC EDUCATION FOR HOMO DIGITALIS - Mamat Rahmat; Ahmad Zaky Zakaria Anshary; Adang Hambali; Andewi Suhartini (Academic Bright Collaboration, 2026)
This study aims to develop a comprehensive model of Islamic education grounded in Digital-Theological Consciousness that addresses the ontological transformation of Muslim learners who inhabit digital culture as Homo Digitalis. The research responds to a significant gap in the literature: while digital Islamic education studies have proliferated, none has systematically integrated the philosophical concept of Homo Digitalis with tawhid-based theology into a coherent educational model. A qualitative library research design was employed, drawing on systematic analysis of primary and secondary sources in Islamic educational philosophy, digital theology, and philosophical anthropology. Sources were selected from peer-reviewed journals indexed in Scopus, Web of Science, and Sinta (2020–2025), supplemented by seminal theoretical works from Capurro (2017), Kultaieva (2020), and Phillips et al. (2019). Data were analyzed using an integrative-interpretive approach. The study identifies three foundational gaps in existing scholarship: the absence of Islamic digital theology as a field, the non-integration of Homo Digitalis into Islamic anthropological-educational discourse, and the operational limitation of tawhid-based models in addressing digital consciousness. Based on these gaps, the study proposes the DTC Model comprising five interrelated pillars: Tawhidic Ontological Grounding, Digital Fitrah Literacy, Khalifah-Oriented Digital Ethics, Integrative Epistemology of Revelation and Reason, and Transformative Pedagogical Practice. The model offers a theoretically rigorous and practically applicable framework for Islamic educational institutions navigating digital transformation. Limitations include the conceptual-library nature of the study, which requires empirical validation through subsequent field research in Indonesian madrasah and pesantren contexts. This article introduces Digital-Theological Consciousness as a new construct in Islamic educational theory, offering the first systematic integration of Homo Digitalis philosophy with tawhidic epistemology in educational modelling. The study contributes both to Islamic educational philosophy and to the broader global discourse on religion and digital culture.